2016
DOI: 10.1007/s40806-016-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Casual Sex and College Students: Sex Differences and the Impact of Father Absence

Abstract: Recently, much attention has been focused on understanding casual sex, or hooking up, among college students. The current study uses an adaptationist approach to investigate sex differences in casual sex behavior, emotional reactions, and the influence of father absence. If males and females possess different emotional mechanisms designed to evaluate the consequences of sexual behavior, we would expect sex differences in emotional reactions following that behavior. A sub-theory of life history strategy, psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although the body of literature is less voluminous, father absence also has been related to other indicators of sexual behavior, such as higher number of sexual partners, higher intrasexual competitiveness, and higher jealousy among young people from the United States and Curaçao (Salmon et al, 2016; Schlomer et al, 2019; Van Brummen-Girigori & Buunk, 2016; Van Brummen-Girigori et al, 2016). Furthermore, father absence has been linked to lower educational attainment, more negative social-emotional outcomes such as increased externalizing problem behavior, and more financial hardship while growing up among young people from the United States (McLanahan et al, 2013).…”
Section: Effects Of Father Absencementioning
confidence: 99%
“…Although the body of literature is less voluminous, father absence also has been related to other indicators of sexual behavior, such as higher number of sexual partners, higher intrasexual competitiveness, and higher jealousy among young people from the United States and Curaçao (Salmon et al, 2016; Schlomer et al, 2019; Van Brummen-Girigori & Buunk, 2016; Van Brummen-Girigori et al, 2016). Furthermore, father absence has been linked to lower educational attainment, more negative social-emotional outcomes such as increased externalizing problem behavior, and more financial hardship while growing up among young people from the United States (McLanahan et al, 2013).…”
Section: Effects Of Father Absencementioning
confidence: 99%
“…Additional research has linked father absence with various aspects of girls’ sexual behaviors, including earlier sexual onset (Ellis et al, 2003; Zimmer-Gembeck & Helfand, 2008), more casual sex (Salmon, Townsend, & Hehman, 2016), and more sexual partners (Quinlan, 2003). One prediction that naturally stems from these findings is that the effects of father absence on girls’ sexual behaviors should be mediated, at least partially, by AAM.…”
Section: Father Absence and Reproductive Developmentmentioning
confidence: 99%
“…It may also be possible that father absence may be more important for the prevalence of sexual behaviors relative to its onset, such as when father absence leads to lower parental monitoring and higher affiliation with sexually promiscuous peers (DelPriore et al, 2017). Finally, recent research has suggested that using a continuous measure of father absence that reflects the amount of time spent in a father present household can extend father absence research beyond the focus on early adversity by including a wider age-range (Salmon et al, 2016), which could be relevant for age at first sex. Unfortunately, the present data do not permit this type of variable to be adequately constructed, though continuous father absence should be evaluated in future father absence work.…”
Section: Father Absence Life History Strategies and Geneticsmentioning
confidence: 99%
“…Although recent work criticizes the validity of applying LHT to trait variation within humans (e.g., Nettle and Frankenhuis, 2019;Zietsch and Sidari, 2019), this predictive lens has been useful for studying psychosocial developmental plasticity within underprivileged environments (see Kuzawa and Bragg, 2012). Relative to a slow life history strategy, people with faster life history strategies prefer immediate over delayed rewards (Griskevicius et al, 2011), reproduce earlier (Boothroyd et al, 2013;Hehman and Salmon, 2019), have more casual sex (Dunkel et al, 2015;Salmon et al, 2016), experience earlier sexual debut and report greater sexual risk-taking (James et al, 2012), pursue social status via dominance rather than prestige (Lukaszewski, 2015), score higher on measures of psychopathy (e.g., boldness, aggression, and disinhibition; Mededović, 2018) and dark personality (i.e., impulsivity, antisociality, entitlement/exploitativeness, Machiavellianism, and aggression;McDonald et al, 2012), and are more likely to use psychoactive substances (Richardson et al, 2014). These traits are advantageous in harsh, unpredictable environments to the extent that they help an individual to competitively capitalize on limited resources.…”
Section: Introductionmentioning
confidence: 99%